Integration of Akhlak Values in the Education System: A Terminological and Etymological Review of Character Education - Atina Zainal Fuadah; Devi Rahma Amaliyah; Gefira Eknandina; Moh Faizin (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to explore the integration of moral values in character education from the perspective of Islamic Religious Education, analyze the concepts of tarbiyah, ta’lim, and ta’dib, and examine their relevance in strengthening students’ moral identity in the digital era. Methodology: This study employed a qualitative library research method using descriptive-analytical and interactive analysis models by Miles, Huberman, and Saldaña. Data sources included the Qur’an, Hadith, Ibn Miskawaih’s Tahdzib al-Akhlaq wa Tathir al-A'raq, scientific journals, educational policy documents, and character education textbooks. Data were collected through documentation, literature review, content analysis, triangulation techniques, and expert validation. Main Findings: The study found that character education in Islam requires the integration of moral values through the epistemological trilogy of tarbiyah, ta’lim, and ta’dib. The internalization of character occurs through a holistic spiral process involving cognitive, affective, and psychomotor domains. The findings also revealed that moral resilience in the digital era depends on the internalization of hay’ah (stable moral disposition), not merely on technical digital literacy or formal compliance-based education. Novelty/Originality of this study: This study offers a new conceptual framework by reconstructing tarbiyah, ta’lim, and ta’dib into an integrated epistemological trilogy of Islamic character education. It also introduces a spiral internalization model and theorizes digital moral resilience based on hay’ah. These contributions advance Islamic character education studies beyond normative and technical approaches toward a more philosophical, holistic, and paradigmatic perspective.